1991
DOI: 10.1109/3.89994
|View full text |Cite
|
Sign up to set email alerts
|

Injection locking in distributed feedback semiconductor lasers

Abstract: Abstract-Injection locking properties of distributed feedback semiconductor lasers are studied systematically. Due to the high side mode suppression, these devices show different locking properties when compared to lasers having Fabry-Perot structures. The main result is the identification of four regimes for different injection levels. In particular, a symmetrical locking band at low optical injection level is confirmed. The presence of this symmetrical band can be exploited in some applications: as examples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…Full and open diamonds at negative detuning mark the boundaries of a region of bistability between the locked steady state and a periodic orbit (associated with four-wave mixing). This bistability phenomenon was observed in [7] and then it was studied numerically in [8], but the authors did not recognise the underlying bifurcation mechanism. This motivated the asymptotic analysis in [9], which revealed the existence of a torus bifurcation curve for negative detunings.…”
Section: Bistability At the Locking Boundarymentioning
confidence: 99%
“…Full and open diamonds at negative detuning mark the boundaries of a region of bistability between the locked steady state and a periodic orbit (associated with four-wave mixing). This bistability phenomenon was observed in [7] and then it was studied numerically in [8], but the authors did not recognise the underlying bifurcation mechanism. This motivated the asymptotic analysis in [9], which revealed the existence of a torus bifurcation curve for negative detunings.…”
Section: Bistability At the Locking Boundarymentioning
confidence: 99%
“…Phase noise of injection-locked lasers has been the subject of intensive previous study [20,21,22,23,24,25,26,27,28,29]. It was found that the slave laser phase follows only the phase fluctuations of the master laser, so the slave laser linewidth will be equal to the linewidth of the master laser, independent of the output power of the slave laser.…”
Section: Phase Noise Analysis Of Injection-locked Lasersmentioning
confidence: 99%
“…Pulsations induced by optical injection have also been found to yield information about the important coupling between amplitude and phase of the electric field in a semiconductor laser. In fact, a method was developed to measure the laser linewidth enhancement factor a using injection locking techniques [29].…”
Section: Introduction To Injection-locking Of Semiconductor Lasersmentioning
confidence: 99%
“…In previous works, different kinds of semiconductor optical injected lasers have been investigated (Hui et al, 1991;Chang et al, 2003;. However, the investigations were mainly concerned about single-beam injected lasers.…”
Section: Optical Spectrum Analysis Of the Optical Multi-beam Injectedmentioning
confidence: 99%